DARI STRES KE KESEIMBANGAN: PERAN WISATA SPIRITUAL DI UBUD DALAM PROSES PEMULIHAN DIRI WISATAWAN - Putu Eka Wirawan (Media Bina Ilmiah, 2025)
This study aims to explore the role of spiritual tourism in Ubud, Bali, in supporting the self-healing process of tourists dealing with stress and emotional exhaustion. Using a qualitative approach with phenomenological methods, the research investigates the personal experiences of tourists who participated in spiritual activities such as melukat (Balinese purification ritual), meditation, and yoga at various spiritual centers in Ubud. Data were collected through in-depth interviews, participant observation, and documentation, then analyzed using interpretative phenomenological analysis (IPA). Findings reveal that spiritual tourism provides a significant psychological impact, particularly through emotional catharsis, self-reflection, and increased inner awareness. The melukat ritual offers a profound emotional release, while yoga and meditation help tourists regain mental balance and clarity. The natural environment of Ubud, with its serene landscapes, contributes to psychological restoration, supporting Kaplan & Kaplan’s Attention Restoration Theory. Furthermore, social connections formed during spiritual activities create a sense of belonging and shared healing experiences. This study reinforces existing theories in environmental psychology and transformational tourism and provides new insights through the lived narratives of spiritually engaged tourists. The findings highlight the importance of authentic and culturally-rooted spiritual tourism in creating long-term personal transformation and psychological well-being.